Non-cognitive skills and other related concepts: Towards a better understanding of similarities and differences - Maria Cinque; Stephanie Carretero; Joanna Napierala (European Commission, Joint Research Centre (JRC), 2021)
The aim of this working paper is to discuss the existing terminology, taxonomies, frameworks and concepts used for non-cognitive skills contained in the literature on labour market and skills published between 2009 and 2019, as well as in international policy driven research, with a specific focus on European frameworks. In the comparison of different Socio-emotional Learning (SEL) models we took advantage of the tools created by Harvard University (Explore SEL). Our perspective is descriptive rather than prescriptive as we compared the most important frameworks, highlighting the different perspectives of using dissimilar - and sometimes contrasting - terminologies, the labels and definitions. We suggest a three-dimensional taxonomy composed by the economic, the social and the humanity discourses as first dimension, the global, national and personal perspectives as a second one and the labour market, education policies, personal development drivers as a third one.
Keywords: 330; Non-cognitive Skills; Big Five; Cognitive Skills; 21st Century Skills; Social and emotional skills; Labour market; Taxonomy; Framework